Essential medicines: An Indian perspective - Rituparna Maiti; Vikas Bhatia; Biswa Mohan Padhy; Debasish Hota (Wolters Kluwer Medknow Publications, 2015)
The concept of defining essential medicines and establishing a list of them was aimed to improve the availability of affordable medicines for the world's poor. Access to essential medicines is a major determinant of health outcomes. Several countries have made substantial progress towards increasing access to essential medicines, but access to essential medicines in developing countries like India is not adequate. In this review we have tried to present the Indian scenario in respect to availability and accessibility of essential medicines over last one decade. To enhance the credibility of Indian healthcare system, procurement and delivery systems of essential medicines have to be strengthened through government commitment, careful selection, adequate public sector financing, efficient distribution systems, control on taxes and duties, and inculcating a culture of rational use of medicines in current and future prescribers.